Fabrication of ZnO:Ag/GO composite thin films for enhanced photocatalytic activity. Issue 13 (September 2017) - Ravichandran, K.; Uma, R.; Sriram, S.; Balamurgan, D.
Abstract: Zinc Oxide (ZnO), ZnO/GO (Graphene Oxide) and ZnO:Ag/GO nanocomposite thin films were deposited on glass substrates using a simple cost-effective automated jet nebulizer spray pyrolysis technique for photocatalytic degradation of organic dyes. The ZnO:Ag/GO film exhibits superior photocatalytic activity when compared with ZnO and ZnO/GO films. The degradation rate constant values of pristine ZnO and ZnO/GO films are found to be 0.0143 and 0.0176 min −1, respectively whereas that of ZnO:Ag/GO is 0.0567 min −1 . The possible mechanism involved in the enhanced photocatalytic activity of ZnO:Ag/GO films for the degradation of Methylene Blue dye is proposed with the help of structural, optical and photoluminescence studies. The powder XRD profile confirms the hexagonal wurtzite structure of the synthesized catalysts. The results of Raman, XPS and EDX studies confirm the presence of GO in the ZnO/GO and GO and Ag in the ZnO:Ag/GO films.